Pengaruh Teori Kant dalam Pengembangan Pemikiran Filsafat Hukum Universal : The Influence of Kant's Theory on the Development of Universal Legal Philosophical Thought - Fran Nurmansyah; Dominikus Rato; Fendi Sertyawan (Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2023)
The philosophy of law has developed significantly over time, and many figures have made important contributions to its development. One significant figure who has had a great influence on the development of legal philosophy is Immanuel Kant. Kant was an 18th-century German philosopher famous for his works on epistemology, ethics, and aesthetics. Kant's theory of law and justice has influenced the development of a legal philosophy movement known as